The effect of oral prednisolone on gas exchange in chronic bronchial asthma. - Ellul-Micallef, R (1980)
Patients with bronchial asthma frequently have a fall in arterial oxygen tension following bronchodilator treatment in spite of a reduction in airway resistance. Administration of 0.11 mM (40 mg) prednisolone in a single dose resulted in an improvement of both airway obstruction and hypoxaemia in chronic asthmatic patients. The arterial oxygen tension, alveolar-arterial oxygen tension difference and venous admixture effect all showed a statistically significant improvement as did the dynamic lung volumes and specific airway conductance.